ADAM10-Initiated Release of Notch Intracellular Domain Regulates Microtubule Stability and Radial Migration of Cortical Neurons. (3rd February 2017) - Yang, Zhi; Li, Peng-Fei; Chen, Ren-Chao; Wang, Jie; Wang, Shaoran; Shen, Ya; Wu, Xiaohui; Fang, Bing; Cheng, Xuewen; Xiong, Zhi-Qi
Abstract: Proper neuronal migration is orchestrated by combined membrane signal paradigms, whereas the role and mechanism of regulated intramembrane proteolysis (RIP) remain to be illustrated. We show here that the disintegrin and metalloprotease-domain containing protein 10 (ADAM10) regulates cortical neurons migration by initiating the RIP of Notch. We found that Notch intracellular domain (NICD) significantly rescued the migration defect of ADAM10-deficient neurons. Moreover, ADAM10 deficiency led to reduced neuronal motility and disrupted microtubule (MT) structure, which were associated with downregulated expression of acetylated tubulin and MT-associated proteins. Specifically, the NICD/RBPJ complex bound directly to the promoter, and regulated the neuronal expression level of doublecortin (DCX), a modulator of the MT cytoskeleton. Functionally, DCX overexpression largely restored neuron motility and reversed migration defect caused by ADAM10 knockout. Taken together, these findings demonstrate the direct requirement of ADAM10 in cortical radial migration and reveal the underlying mechanism by linking ADAM10-initiated RIP of Notch to the regulation of MT cytoskeleton through transcriptional control of Dcx expression.